Promising varieties of sour cherry Prunus cerasus L. with a complex of fruit quality traits for growing in the southern Russia - Rimma Sh. Zaremuk; Tatiana A. Kopnina (RUDN Journal of Agronomy and Animal Industries, 2022)
Southern assortment of cherries does not quite meet the modern requirements of production. Many varieties are low-productive, not resistant to cherry leaf spot ( Coccomyces hiemalis ) and moniliosis ( Monilia cinerea ), small-fruited, with low taste qualities. However, new varieties have been created that have not been studied by the complex of consumer and commodity qualities of fruits. Thus, evaluation of new varieties for these traits is relevant. The aim of the research was to evaluate cherry varieties of different origin for commodity, biochemical, and consumer qualities of fruits. The research was carried out in the Kuban horticultural zone of the Krasnodar territory. Objects of the research were 9 varieties of sour cherry trees. Field and laboratory studies were conducted according to Program and methodology of varietal study of fruit, berry and nut crops (1999), Methodological instructions on chemical and technological variety testing of vegetable, fruit and berry crops for canning industry (1993). Statistical analysis was carried out according to B.A. Dospekhov (2014) and G.F. Lakin (1990). It was found that the average fruit weight of cherry varieties varied not significantly - from 2.72 to 6.45 g, which was confirmed by the coefficient of variation (23.3 %). Indicators of maximum and minimum fruit weight varied significantly in varieties, coefficients of variation were 27.2 and 29.7 %, respectively. The following cherry varieties with large fruits were identified: Timati, Igrushka, Duk Ivanovna, Duk Khodosa, Prizvaniya and Svetlaya. were distinguished. Cherry varieties with high sugar content in fruits were as follows: Feyа, Dzhusi Frut and Igrushka. Feyа, Duk Khodosa, Prizvanie, Svetlaya and Dzhusi Frut had fruits with low acidity; Feyа, Dzhusi Frut and Igrushka fruits were characterized by high content of soluble solids in fruits. Feyа, Igrushka and Duk Khodosa fruits had the highest content of vitamin C; Igrushka, Duk Khodosa, Prizvanie, Svetlaya and Dzhusi Frut were rich in Vitamin P; Duk Khodosa, Prizvanie, Dzhusi Frut and Duk Ivanovna had the largest anthocyanin content. Therefore, Igrushka and Duk Khodosa cherry varieties are recommended for growing in the southern Russia and breeding for improvement of fruit quality.